Configurational Pathways to Breakthrough Innovation in the Digital Age: Evidence from Niche Leaders - Shuai Liao; Xi Deng; Hui Lu; Luyao Niu (Systems)
Fostering niche leaders to achieve technological breakthroughs has become a national strategic priority in emerging markets in order to overcome technology blockades and drive technological progress. Previous research indicates that achieving breakthrough innovation, particularly for firms with resource constraints, is a multifaceted phenomenon occurring across various levels. Based on the technology–organization–environment (TOE) framework, this paper aims to examine the influence of technological, organizational, and environmental factors on the breakthrough innovation of niche leaders in emerging markets from a configurational perspective. Using dynamic qualitative comparative analysis (QCA), we analyzed panel data from 87 Chinese niche leaders (2018–2023) through inter-group, intra-group, and pooled comparisons to uncover distinct configurational pathways to breakthrough innovation. Our findings reveal three effective pathways: an R&D-driven innovation pathway, a digital transformation-driven innovation pathway, and a comprehensive support innovation pathway. Additionally, we identified two configurational pathways leading to the absence of high-breakthrough innovation: the conservative management configuration, and the digital island configuration. Our results underscore the essential role of government subsidies, the complementary impact of digital transformation and R&D, and the restrictive effect of rigid governance structures. Furthermore, these pathways demonstrate significant regional variations and temporal evolution, highlighting the context-dependent nature of breakthrough innovation in emerging economies.